Development of Antioxidant Multilayer Film with Compostable Properties, Based on Polylactic Acid, Mater-Bi, and Eugenol - Guarda-Moraga, A; Bruna-Bugueno, J (Springer, 2026)
This study reports the development and characterization of fully compostable multilayer films with antioxidant functionality. The multilayer structure consists of an outer layer of Mater-Bi® (MB), an inner active blend of polylactic acid and eugenol (PLA/Eu), and a whey protein isolate (WPI)-based adhesive interlayer. The films were characterized in terms of optical, mechanical, thermal, and barrier properties, as well as by FTIR spectroscopy, overall migration, and compostability assessment. Morphological analysis confirmed good interfacial compatibility and successful layer assembly. The active multilayer film (MB-WPI-PLA/Eu) exhibited a tensile strength of 34 ± 4 MPa, showing an improvement over the MB monolayer (24 ± 5 MPa). It also displayed low oxygen permeability (74 ± 19 cm3m⁻2day⁻1) and water vapor transmission (144 ± 4 gm⁻2day⁻1), representing a considerable reduction compared to the MB monolayer film (OTR = 356 cm3m⁻2day⁻1 and WVP = 278 gm⁻2day⁻1), indicating good barrier performance suitable for food packaging applications. The antioxidant activity of the active PLA/Eu layer reached 81 ± 1.2% RSA after 72 h, confirming the effective release of eugenol and its antioxidant functionality. Overall migration tests with fatty food simulants resulted in values below the regulatory limit of 10 mgdm⁻2, ensuring suitability for food contact. Composting tests demonstrated complete disintegration of multilayer materials within 90 days under controlled composting conditions. Moreover, the resulting compost had no adverse effects on seed germination or the early growth of maize and radish plants, confirming its environmental safety. These results highlight the potential of the developed multilayer system as an eco-friendly packaging solution for high-fat food products. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.